Stability of NaO2 and LiO2 discharge products in metal-air batteries: density functional theory study - Ramogayana Brian; Maenetja Khomotso P.; Ngoepe Phuti E. (MATEC Web of Conferences, 2023)
Rechargeable metal-air batteries are considered the next generation energy storage devices with the highest energy density of ~200 Wh/kg (which is much higher than the Li-ion batteries with ~150 Wh/kg). However, their practical applications are widely affected by the formation of unstable discharge products (like Na/LiO2, Na/Li2O, and Na/LiO) which react with electrolyte or the porous electrode material leading to either fire or explosion. Here, we explore the stability of the bulk pyrite and marcasite lithium/sodium superoxide (Li/NaO2) discharge products produced in Li and Na-air batteries using density functional theory calculations. The calculated lattice and heats of formations are consistent with available reported data. The electronic properties of show the Pnmm LiO2 as the most stable structure with the least density of states at the Fermi. The vibrational properties also show no imaginary vibrations in all directions for Pnmm LiO2. This finding can help direct and give an insight into the stability of major discharge products and give research direction towards controlling the formation of desired M-O discharge products in the batteries.